디지털 서비스 활용에 있어서의 시니어 사용자 경험 향상을 위한 감성 UX 디자인 방향성 연구 - ADL 기준에 따른 디지털 헬스케어 중심으로 - 고은희; Eunhee Koh; 조아라; Ara Cho; 이인호; Inho Lee; Ara Cho (한국디자인포럼, 2025)
연구배경 급격한 고령화 시대에 접어들면서 시니어층의 디지털 서비스 접근성 및 사용성이 중요한 문제로 대두되고 있다. 그러나 기존의 디지털 서비스는 기술적 요소에 치중되어 시니어 사용자의 감성적 경험이 충분히 반영되지 못하고 있다. 본 연구는 시니어 사용자 경험(UX)의 감성적 요인의 중요성을 검증하고 그 방향성을 제시하고자 한다. 연구방법 이론적 고찰을 통하여 시니어의 디지털 사용자 경험의 특성과 감성적 사용자 경험 요인을 분석하였다. 실증 연구에서는 4개 디지털 서비스를 선정하여 에스노그래피 리서치를 진행하였으며 26명의 시니어와 4명의 시니어 케어 제공자를 대상으로 비언어적 관찰법(포토 다이어리)과 언어적 관찰법(심층 인터뷰)을 병행하였다. 이후 포커스 그룹 토론(FGD)을 통해 시니어의 디지털 사용자 경험 요인 중 감성적 기준의 사용자 경험요인의 중요도를 검증하고 그 원인을 분석하였다. 연구결과 스마트 링, 스마트 약통, 공기청정기 및 모니터링 서비스, 스마트 글러브 4가지 디지털 서비스에서 감성적 평가 요인인 긍정적 기대감, 연결감, 자기결정감이 상위 평가 요인에 포함되었으며, 이를 통해 기술적요인 뿐 아니라 감성적 요인이 시니어의 사용자 경험에 유의미한 영향을 미칠 수 있음을 도출하였다. 결론 시니어의 디지털 서비스에서 감성적 사용자 경험요인이 기능적 요인과 함께 필수적으로 고려되어야 함을 확인하였으며, 감성적 요인이 고려된 사용자 경험의 방향성을 제시하였다. 이를 통해 디지털 서비스가 시니어 사용자의 삶의 질 향상과 사회적 소외감 해소에 기여할 수 있을 것으로 기대된다. Background As societies age, the usability of digital healthcare services has become crucial for improving seniors' health and quality of life. However, these services often prioritize technical aspects over emotional experiences, limiting their effectiveness. This study validates the importance of emotional factors in senior user experience (UX) and suggests integration strategies. Methods The study employed both theoretical review and empirical research. In the theoretical review, the characteristics of senior user experiences and emotional user experience factors were analyzed. For the empirical research, ethnographic research methods were applied to four digital services, involving 26 seniors and 4 senior care providers. Both non-verbal observation methods (photo diaries) and verbal observation methods (in-depth interviews) were conducted in parallel. Subsequently, a focus group discussion (FGD) was held to identify key factors of senior user experience and determine their priority rankings. Result Emotional evaluation factors such as positive expectations, connectedness, and self-determination were identified as top-ranking factors across four digital services― smart rings, smart pillboxes, air purifiers, and smart gloves. This indicates that emotional factors may have a greater impact on senior user experience than technical factors. Conclusion In conclusion, the study confirmed that emotional user experience factors must be considered alongside functional factors in digital services. It also proposed a user experience direction that incorporates emotional considerations for future development. These findings suggest that digital services can contribute to improving the quality of life for senior users and alleviating social isolation.